Genetically stable kill-switch using “demon and angel” expression construct of essential genes - Kato, Yusuke; Mori, Hirotada (Frontiers in Bioengineering and Biotechnology, 2024)
Genetic instability of synthetic genetic devices is a key obstacle for practical use. This problem is particularly critical in kill-switches for conditional host killing. Here, we propose a genetically stable kill-switch based on a "demon and angel" expression construct of a toxic essential gene. The killswitch conditionally overexpresses the toxic essential gene. Additionally, the identical essential gene is deleted in the genome. The essential gene is expressed at a low level to maintain host survival in the OFF state and kills the host by the overexpression in the ON state. The single expression construct is responsible for both killing the hosts and maintaining viability, reducing the emergence of loss-of-function mutants. We constructed the kill-switch using the toxic essential gene encoding tyrosyl-tRNA synthetase, tyrS, in Escherichia coli. The bacteria harboring the kill-switch were conditionally suicidal over 300 generations. Toxic overexpression of essential genes has also been found in other organisms, suggesting that the "demon and angel" kill switch is scalable to various organisms.